Hubungan antara Locus of Control dengan Regulasi Diri dalam Belajar pada Mahasiswa yang Sedang Mengerjakan Skripsi - Togatorop, Bawadi; Rusli, Devi (YASIN, 2024)
Students are part of educational institutions that are required to excel in both academic and non-academic fields. The objective of this research is to examine the relationship between locus of control and self-regulated learning in students who are working on their thesis. The method used in this study is a quantitative approach with product moment correlation analysis. The sample size for the research consists of 384 students working on their thesis at Universitas Negeri Padang, using simple random sampling technique. The measurement tool for locus of control consists of three dimensions with the following reliability: internal locus of control (internality) has a Cronbach’s alpha of 0.375, external locus of control (powerful others) has a Cronbach’s alpha of 0.869, and external locus of control (chance) has a Cronbach’s alpha of 0.811. Meanwhile, the reliability of self-regulated learning has a Cronbach’s alpha of 0.859. From the analysis using Spearman’s product moment, locus of control is divided into three dimensions: Internal (I) obtained a significant result with a score of 0.000 < 0.05, while the external dimension of Powerful Others (P) obtained a non-significant result with a score of 0.081 > 0.05, and the Chance (C) dimension obtained a significant result with a score of 0.003 < 0.05. This indicates that there is a significant positive relationship between locus of control and self-regulated learning among students who are working on their thesis at Universitas Negeri Padang.